2022
DOI: 10.3390/plants11233341
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extract of Artemisia annua Shows In Vitro Antimicrobial Activity and an In Vivo Chemopreventive Effect in a Small-Cell Lung Cancer Model

Abstract: Artemisia annua (A. annua) has been used as a medicinal plant in the treatment of several infectious and non-infectious diseases in the forms of tea and press juice since ancient times. The aim of this study was to evaluate the aqueous extract of A. annua (AAE) as an antimicrobial agent in vitro and to evaluate its chemopreventive efficacy in vivo in a small-cell lung cancer (SCLC) animal model. The dried powder of AAE was prepared using the Soxhlet extraction system from the leaves of Artemisia annua. The in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…Aqueous extract of Artemisia annua played a preventive role against malignancy in the lung cancer models. It also induced apoptosis and decreased intracellular reactive oxygen species (ROS) in the lung cells ( Allemailem, 2022 ). Peng et al ( Peng et al, 2021 ) revealed that the combination of anlotinib and Brucea Javanica Oil (BJO) significantly inhibited the growth of SCLC liver metastases and angiogenesis more than anlotinib monotherapy.…”
Section: Treatment Of Lung Cancer With Traditional Chinese Medicine E...mentioning
confidence: 99%
“…Aqueous extract of Artemisia annua played a preventive role against malignancy in the lung cancer models. It also induced apoptosis and decreased intracellular reactive oxygen species (ROS) in the lung cells ( Allemailem, 2022 ). Peng et al ( Peng et al, 2021 ) revealed that the combination of anlotinib and Brucea Javanica Oil (BJO) significantly inhibited the growth of SCLC liver metastases and angiogenesis more than anlotinib monotherapy.…”
Section: Treatment Of Lung Cancer With Traditional Chinese Medicine E...mentioning
confidence: 99%
“…The antifungal capabilities of Seriphidium herba-alba (Asso) are equally significant, particularly considering the limitations and side effects of many synthetic antifungal drugs. Research has shown that Artemisia extracts can inhibit fungi such as Candida albicans , which cause infections in immunocompromised individuals [ 9 ], and their efficacy against molds such as Penicillium and Aspergillus suggests their potential use as natural food preservatives [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…absinthium is among the therapeutic plants that are used in traditional healthcare, and numerous studies have been conducted on it, to determine the extent to which it has inhibitory and antibacterial properties. A thorough review of the literature on A. absinthium's phytochemical data reveals that their principal constituents are polyphenolics, terpenoids, flavonoids, coumarins, caffeoylquinic acids, sterols, and acetylenes, which are responsible for the reduction process [37][38][39].…”
Section: Introductionmentioning
confidence: 99%